Hearing loss in ankylosing spondylitis. (6th May 2019) - Ajmani, Sajal; Keshri, Amit; Srivastava, Rakesh; Aggarwal, Amita; Lawrence, Able
Abstract: Aim: Several studies have described sensorineural deafness in ankylosing spondylitis (AS) patients while conductive hearing loss has been reported to be rare. In our study we have studied the prevalence of hearing loss (HL) among AS patients and its association with non‐steroidal anti‐inflammatory drug (NSAID) intake. Methods: We studied 100 AS patients and 40 controls. HL was defined as pure‐tone thresholds greater than 20 dB (decibel) in at least two frequencies of the audiogram. Severity of HL was defined as given by World Health Organization. Clinical details and cumulative NSAID doses were noted. Results: Ninety‐six of the 100 patients were male with mean age of 32 ± 12 years and mean duration of illness of 8.2 ± 6 years. Median Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI) and cumulative NSAID dose were 3.5 ± 2.2, 2.75 ± 2, 3.7 ± 2.6 and 1202 ± 1290, respectively. Of the 48 with HL, 28 patients had bilateral HL. Twenty‐nine patients had pure conductive HL while 16 had mixed HL (components of both sensory and conductive) and 3 had pure sensorineural HL. HL was mild in 38 patients, and moderate to severe in 10 patients. The presence of HL was associated with higher age ( P ≤ 0.05). Conductive HL was at low frequency (0.25, 0.5, 1 kHz) in 70% of cases. Sensorineural HL was at high frequency (4, 8 kHz) in 75% of cases. There was no association of HL with disease parameters such as BASMI, BASDI, BASFI or cumulative NSAID dose. Conclusion: HL is common in AS. Conductive HL is more common than sensorineural HL. It is usually mild and occurs at low frequencies.